2014
DOI: 10.1074/jbc.m113.512277
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines Alter IgA1 O-Glycosylation by Dysregulating C1GalT1 and ST6GalNAc-II Enzymes

Abstract: Background: IgA1-producing cells of IgA nephropathy patients secrete IgA1 with galactose-deficient O-glycans; these IgA1 molecules form nephritogenic immune complexes.Results: Cytokines IL-6 and IL-4 accentuate IgA1 galactose deficiency via modulation of key glycosyltransferases.Conclusion: Some cytokines alter IgA1 O-glycosylation and increase production of nephritogenic IgA1 glycoforms.Significance: These data provide a mechanism explaining increased immune-complex formation in IgA nephropathy patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
157
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(161 citation statements)
references
References 92 publications
(128 reference statements)
2
157
1
1
Order By: Relevance
“…These in silico predictions coupled with previous in vitro data demonstrating modulation of IgA1 O-galactosylation by Th2 cytokines and IL-6 36,37 , as well as our previous observation that IgA1 O-galactosylation varies depending on the site of antigen encounter and B cell activation 38 , are consistent with an effect of the H1 haplotype on transcriptional control of C1GALT1 particularly in IgA1-committed B cells.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…These in silico predictions coupled with previous in vitro data demonstrating modulation of IgA1 O-galactosylation by Th2 cytokines and IL-6 36,37 , as well as our previous observation that IgA1 O-galactosylation varies depending on the site of antigen encounter and B cell activation 38 , are consistent with an effect of the H1 haplotype on transcriptional control of C1GALT1 particularly in IgA1-committed B cells.…”
Section: Discussionsupporting
confidence: 68%
“…Cytokines, and presumably other stimuli, acting in B cells can influence IgA1 galactosylation 37 , and likely contribute to the variability in Gd-IgA1 levels. Identification of the transcriptional mechanisms influencing C1GALT1 expression may provide insights into how Gd-IgA1 levels are controlled in health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that cytokines, including interleukin-4 and interleukin-6, increased the production of GdIgA in Epstein-Barr virusimmortalized B cells from IgAN patients; and it is intriguing that interleukin-6 also increased the GdIgA level in healthy individuals. 23 In contrast to these findings regarding cytokines, our data, based on flow cytometry, real-time quantitative PCR, and RNA sequencing, do not support the notion that TNFSF13 dose of rhTNFSF13 used was 0.2 mg/ml. The doses of the receptor blockers were 5 mg/ml.…”
Section: Discussioncontrasting
confidence: 52%
“…An increase of Tn antigen on the T cell surface could be related to a reduced expression of the enzyme C1GalT1 or its molecular chaperone Cosmc, which has been reported to be altered by the presence of cytokines such as IL-6 and IL-4 (Suzuki et al 2014;Yamada et al 2010 (Yamada et al 2010), which could explain the alterations of core 1 expression on CD4 + T cells from active SLE patients that we described herein.…”
Section: Discussionmentioning
confidence: 55%